Alphavirus protease inhibitors from natural sources: A homology modeling and molecular docking investigation. (October 2016) - Byler, Kendall G.; Collins, Jasmine T.; Ogungbe, Ifedayo Victor; Setzer, William N.
Graphical abstract: Highlights: Alphavirus infections are neglected tropical diseases for which there are no antiviral therapies or vaccines available. The non-structural protein 2 (nsP2) protease is considered to be a promising target for antiviral drug discovery. A molecular docking analysis of 2174 plant-derived natural products with alphavirus nsP2 proteases has been carried out. A total of 127 phytochemical ligands have shown promising docking affinities to one or more of the nsP2 proteases. Abstract: Alphaviruses such as Chikungunya virus (CHIKV), O'Nyong–Nyong virus (ONNV), Ross River virus (RRV), Eastern equine encephalitis virus (EEEV), Venezuelan equine encephalitis virus (VEEV), and Western equine encephalitis virus (WEEV), are mosquito-transmitted viruses that can cause fevers, rash, and rheumatic diseases (CHIKV, ONNV, RRV) or potentially fatal encephalitis (EEEV, VEEV, WEEV) in humans. These diseases are considered neglected tropical diseases for which there are no current antiviral therapies or vaccines available. The alphavirus non-structural protein 2 (nsP2) contains a papain-like protease, which is considered to be a promising target for antiviral drug discovery. In this work, molecular docking analyses have been carried out on a library of 2174 plant-derived natural products (290 alkaloids, 664 terpenoids, 1060 polyphenolics, and 160 miscellaneous phytochemicals) with the nsP2 proteases of CHIKV, ONNV, RRV, EEEV, VEEV, WEEV, as well as Aura virus (AURV), Barmah Forest Virus (BFV), Semliki Forest virus (SFV), and Sindbis virus (SINV) in order to identity structural scaffolds for inhibitor design or discovery. Of the 2174 phytochemicals examined, a total of 127 showed promising docking affinities and poses to one or more of the nsP2 proteases, and this knowledge can be used to guide experimental investigation of potential inhibitors.